Epidemiology of Gastrointestinal Disease among Children and Adolescents in Kazakhstan: 2012–2019 - Zhaksylyk, Alikhan; Nurbakyt, Ardak; Grjibovski, Andrej; Kaussova, Galina; Buleshov , Myrzatai (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Gastrointestinal diseases are important trigger of public health concern in pediatric population. Non treated pathologies led to chronic inflammatory processes in adulthood. AIM: With respect to the lack of international studies on epidemiology of gastrointestinal disease in pediatric population, this study was aimed at analysis of national and local incidence rates of gastrointestinal disorders among children and adolescents in Kazakhstan over the period from 2012 to 2019. METHODS: This was a retrospective cross-sectional study located on South part of Kazakhstan and based on the data obtained from the Republican Center for Health Development – the major data source on the country’s health statistics. From this, we extracted information on children (0–14 years) and adolescents (15–17 years) with gastrointestinal disease (K00-K95 International Classification of Diseases, Revision 10 codes). We calculated incidence rates for the whole country and Turkestan province. RESULTS: The national incidence of pediatric disease was characterized by relative stability, and was 7760.4 per 100,000 population in 2017. The incidence of peptic ulcers and gallbladder disease in adolescents substantially exceeded that in children. At provincial level the incidence of gastritis/duodenitis and peptic ulcers was gradually declining, while that of gallbladder disease was subjected to growth over the past years. Adolescents had higher rates of gastrointestinal disease both at national and provincial levels. CONCLUSION: The analysis of national and local incidence rates of gastrointestinal disorders among children and adolescents in Kazakhstan showed that more studies are needed to obtain in-depth understanding of risk factors associated with gastrointestinal disease in child and adolescent population of Kazakhstan, including the prevalence of Helicobacter pylori infection. Besides, a national registry on pediatric gastrointestinal disease should be envisaged to overcome the lack of essential data.